Multi-Element Composition of Honey as a Suitable Tool for Its Authenticity Analysis - Oroian Mircea; Amariei Sonia; Leahu Ana; Gutt Gheorghe (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to evaluate the composition of 36 honey samples of 4 different botanical origins (acacia, sun flower, tilia and honeydew) from the North East region of Romania. An inductively coupled plasma-mass spectrometry (ICP-MS) method was used to determine 27 elements in honey (Ag, Al, As, Ba, Be, Ca, Cd, Co, Cr, Cs, Cu, Fe, Ga, K, Li, Mg, Mn, Na, Ni, Pb, Rb, Se, Sr, Tl, U, V and Zn). We would like to achieve the following goal: to demonstrate that the qualitative and quantitative multi-element composition determination of honey can be used as a suitable tool to classify honey according to its botanical origin. The principal component analysis allowed the reduction of the 27 variables to 2 principal components which explained 74% of the total variance. The dominant elements which were strongly associated with the principal component were K, Mg and Ca. Discriminant models obtained for each kind of botanical honey confirmed that the differentiation of honeys according to their botanical origin was mainly based on multi-element composition. A correct classification of all samples was achieved with the exception of 11.1% of honeydew honeys.